Radial arrangement of clonally related cells in the chicken optic tectum: lineage analysis with a recombinant retrovirus. - Gray, G E (1988)
A recently described method for lineage analysis in rodents uses a recombinant retrovirus to insert a foreign gene into the genome of a precursor cell; the gene's product is later detected histochemically in the infected cell's progeny. We have adapted this method for use in chicken embryos and used it to study the disposition of clonally related cells in the optic tectum. We report that descendants of a single precursor form narrow, radially oriented columns that span the thickness of the developing tectum. Analysis of embryos injected with virus at different stages suggests a developmental scheme in which early-born progeny are displaced laterally, late-born progeny are displaced radially, and cell mixing is limited. Many clones remain radially arrayed as laminae form and contribute neurons of diverse types of several laminae. In light of previous studies showing physiological relationships among vertically arrayed neurons, our results suggest that neurons descended from a single precursor are richly interconnected and functionally related.